PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi Empiris Terhadap Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Dhita Nugrahing Ramadhani; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2020)
This purpose of the research is to know the effect of GCG mechanism (owner of institutional, owner of managerial, audit committee, delegate of commissary and direction) based on the CSR. Empire study based on the manufacture company which registered in Indonesia Stock Exchange on 2016-2018. This research formulated the proposal as into trouble about the whether the mechanisms corporate governance in also had an impact simultaneously and partial cast against broad the disclosure of CSR. This research is a quantitative study using multiple linier regression test. The data used in the research is secondary data obtained through official website Indonesia Stock Exchange (www.idx.co.id). Data collection techniques used in this research which is our literature and research techniques documentation. The results of this study indicate that institutional ownership, managerial ownership, the board of commissioners partially have no effect on the area of CSR disclosure, while the audit committee and board of directors partially have a positive effect on the area of CSR disclosure. From the results of this study are expected to provide information regarding the role of CSR GCG and can be considered for the company to pay attention to the quality of CSR done. Keywords: Institutional ownership, Managerial ownership, Audit committee, boards of commissioners, board of directors, CSR